Early versus Delayed Excision and Grafting of Full-Thickness Burns in a Porcine Model: A Randomized Study. Issue 6 (June 2016) - Singer, Adam J.; Toussaint, Jimmy; Chung, Won Taek; McClain, Steve A.; Raut, Vivek; Rosenberg, Lior
Abstract : Background: The standard of care for full-thickness burns is tangential excision followed by skin autografting; however, the timing of excision and grafting is subject to debate. The authors compared early (2 days) versus delayed (14 days) excision and grafting in a porcine full-thickness burn model. Methods: Full-thickness burns ( n = 12) were created on the backs of two anesthetized pigs and assigned randomly to no excision, tangential excision followed by skin autografting 2 days after injury, or tangential excision followed by skin autografting 14 days after injury. Digital images and full-thickness biopsy specimens were taken at 16, 21, 28, and 42 days after injury to determine percentage reepithelialization and scar depth. Results: At day 16, all burns that were excised early were completely reepithelialized, whereas only eight of 11 nonexcised burns (72.7 percent) were reepithelialized ( p = 0.02). By day 21, all burns were completely reepithelialized. Scar thickness was greatest at 42 days in nonexcised burns (7.5 ± 2.1 mm); scars were thinner after early excision than after late excision (2.2 ± 1.8 mm versus 4.0 ± 1.1 mm; p < 0.001, analysis of variance). Wounds treated with early or late tangential excision followed by skin autografting were flat and minimally contracted, whereas all nonexcised burns were red, contracted, and slightly raised. Scar contraction at 28 and 42 days was greatest in nonexcised control wounds compared with early and late excised wounds. Conclusions: Both early and late excision followed by autografting reduce scarring in a full-thickness porcine burn model. However, early excision (2 days after injury) reduces scar thickness to a greater extent than later (after 14 days) excision.